MRI Screening of Lungs in the COVID-19 Pandemic at the Stages of Medical Care as a Tool to Reduce the Total Collective Dose of Radiation to the Population - A. V. Korobov; N. V. Nudnov; A. Yu. Popov; T. V. Kul’neva; V. V. Babenko; E. V. Pron’kina (Вестник рентгенологии и радиологии)
Objective: to evaluate the role and place of MRI lung screening in the detection of pneumonia and patient routing.Material and methods. 500 MRI tests were performed in the period from November 1, 2020 to December 15, 2020 on the basis of more than 20 diagnostic centers of the federal MRI-Expert network. Two groups were identified. In Group 1 (control, n = 50) MRI studies were compared with CT studies in a single time interval of 0–2 days; 25 patients had a positive PCR test for SARS-CoV-2 and 25 patients were conditionally healthy. In Group 2 (effective, n = 450) mediastinal MRI was performed with lung screening on Philips 1.5 T and Siemens 1.5 T devices. The statistical analysis of the medical data base was performed.Results. During the study, mandatory and additional MRI scanning programs were identified: for Philips 1.5 T tomograph, the mandatory programs are sSSh_fb: tra and cor; THRIVE: tra (inhale/exhale); for Siemens 1.5 T – T2_BLADE: cor, tra, sag. When comparing the visual data of the control group (n = 25) with a positive PCR test in a single time interval of 0–2 days, the fact of detecting MR changes coincided with CT changes in 76% of cases (n = 19). The group of patients were examined by only one method – MRI-screening of the lungs (n = 475), pathological changes in the lungs were detected in 44% (n = 209). Localizations of the pathological changes were as follows: bilateral changes – 70.3% (n = 147), right-side changes – 19.6% (n = 41), left-side changes – 10% (n = 21); lower parts 26.8% (n = 26), average departments – 10% (n = 21), the upper divisions – 14.8% (n = 31), mid-lower 29.6% (n = 62), total – 18.6% (n = 39). The ranges of the area of lesion of the pulmonary parenchyma on MRI were graded according to MRI criteria into 4 groups (< 25%, 25 – 50%, 50 – 75%, > 75%). The collective radiation dose decrease was calculated for a group of patients (n = 450), which averaged 2.025 man-Sv for 1.5 months, of which 0.077 man-Sv were control studies.Conclusion. Based on the results obtained, the analyses of the possibilities of the MRI method in displaying pulmonary changes was performed. The method of MRI screening of the lungs is recognized as a possible alternative to computed tomography for dynamic monitoring in conditions of a shortage of CT records or the inability to perform it, and as a tool to reduce the collective effective dose of radiation to the population.